Gender Disparities in Earnings Mobility: The Role of Employment Protection Legislation during Reproductive Years in Europe - Bárcena-Martín, Elena María; Medina-Claros, Samuel; Pérez-Moreno, Salvador Jesús (Taylor & Francis, 2025)
This article assesses potential differences in the implementation of employment protection for permanent and temporary contracts on upward and downward in-work earnings mobility between women and men aged 25–40 years in European countries for 2008–2014. Results reveal that, although employment protection is formulated based on a gender-neutral conception, the application of such measures might be associated differently with earnings mobility by gender. While higher levels of protection for regular contracts seem to be linked to lower earnings gains for women and men, more stringent employment regulations are related to losses for women. Likewise, stricter protection of temporary employment appears to favour greater gains for men, while it only prevents women from suffering more pronounced losses. In policy terms, intra-household and societal gender inequities, stand out as key factors driving the links between employment protection and earnings mobility
https://openpolicyfinder.jisc.ac.uk/id/publication/4942
Keywords: Salarios - Diferencias entre los sexos; Transversalidad de género; Mujeres - Salarios; Seguridad en el empleo; Gender; European countries; Earnings mobility; Employment protection